Can anti-Unruh effect survive the environment-induced interatomic interaction? - Ying Chen; Hongwei Yu; Jiawei Hu (Physics Letters B, 2024)
The entanglement generated for a uniformly accelerated two-atom system in vacuum during its evolution may increase with acceleration, while that for a static one in a thermal bath always decreases monotonically with temperature. This phenomenon is named as the anti-Unruh effect in terms of the entanglement generated. In this paper, we study the effects of the interatomic interaction induced by the electromagnetic vacuum fluctuations on the entanglement dynamics of two uniformly accelerated atoms. We show that the anti-Unruh phenomenon may exist or disappear depending critically on the configuration of the orientation of the atomic polarization and the directions of the uniform acceleration and the interatomic separation. This is in sharp contrast to the scalar-field case, in which the anti-Unruh phenomenon is always lost when the environment-induced interatomic interaction is considered.